Data fusion‐aided cognitive radio network over generalised fading channels. Issue 5 (1st March 2019) - Nallagonda, Srinivas
Abstract : In this Letter, the authors study analytical performance of various soft data fusion (SDF) schemes over generalised fading channels in a cognitive radio network. Two generalised fading models, namely, κ − μ and η − μ are considered individually in the sensing channels and various SDF techniques are implemented at the fusion centre. Novel analytical frameworks for cooperative detection probability are developed subject to SDF and generalised fading and validated through computer simulations. Optimal values of the detection thresholds are determined where an average error rate is minimum.